ANALISIS PENGARUH KESADARAN NILAI, PEMENUHAN STATUS SOSIAL, DAN MATERIALISME TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU TIRUAN MEREK TERKENAL (Studi pada Konsumen Sepatu Tiruan Merek Terkenal di Semarang) - Widhi Pangestuti, Aisah; Sukresna, I Made (Diponegoro Journal of Management, 2018)
Counterfeiting of luxury goods is a very profitable business, especially in China, Hong Kong, South Korea, Singapore, Taiwan, Thailand, Malaysia and Indonesia. billion dollars are lost every year because of the manufacture and sale of fake luxury goods. Researchers conducted a survey related to famous brand imitation footwear products. Famous shoe brands in Indonesia used in this study are Nike, Adidas, League, Reebok, Converse, Bata, Kasogi and Puma. The number of samples used was 207 respondents. This study uses analysis techniques of Structural Equation Modeling (SEM) using the AMOS 22.00 analysis tool and is also assisted by analysis using SPSS.The results of this study indicate that value awareness has a positive and significant influence on attitudes toward brands, fulfillment of social status has a positive and not significant influence on attitudes toward brands, materialism has a positive and significant influence on attitudes toward brands and attitudes towards brands have a positive and significant influence towards purchasing decisions.